Stories of wars and “pracinhas”: the Peace Museum, in Jaraguá do Sul, Santa Catarina - Oliveira Neto, Wilson (2022)
The Peace Museum – MPZ was created in 2009 and is considered a Military Museum. The purpose of this article is to analyze the MPZ, highlighting the context of its creation and the way in which the WWII and the BEF are approached in its long-term exhibition. To this end, a survey of primary sources was carried out and the Museum's exhibition itself was analyzed. The MPZ is part of a set of memory spaces related to the Second World War in Jaraguá do Sul and neighboring municipalities. Its creation is linked to the appreciation of the memory of former combatants of the Brazilian Expeditionary Force, which occurs through its long-term exhibition and the educational projects it develops, in addition to its involvement with ephemeris and events related to the history ofthe Second World War.